505PPD-L1 expression in ALK rearranged NSCLC: All questions answered?. (24th November 2019) - Amrith, B P; Sharma, M; Jain, P; Joga, S; Bothra, S J; Jajodia, A; Sood, R; Pasricha, S; Batra, U
Abstract: Background: Treatment of non-small cell lung cancer (NSCLC) has undergone a paradigm shift in the last decade with the advent of targeted therapy and immunotherapy. Anaplastic Lymphoma Kinase (ALK) rearrangement and Programmed Death-Ligand 1 (PD-L1) expression are important predictive biomarkers for response to targeted therapy and immunotherapy respectively. How these two biomarkers interplay with each other is yet to be determined. Various studies have tried to establish a relationship between PD-L1 expression in tumors and treatment outcomes in ALK rearranged NSCLC, with conflicting results. There is a paucity of data regarding this relationship from the Indian subcontinent. Methods: PD-L1 expression was assessed in tissue samples of 58 patients with advanced ALK rearranged NSCLC treated between 2015 and 2018. PD-L1 expression was measured by immunohistochemistry using VENTANA PD-L1 (SP263) antibody on formalin-fixed paraffin-embedded specimens. The epidemiological profile of patients and the relationship between progression free survival (PFS) on small molecule ALK inhibitor and PD-L1 expression were noted. Results: The median age was 47 years (range 25-72 years) and there were 25 males (50%). Most of the patients were never smokers (88%). Thirty-seven (63.7%) of tumors expressed PD-L1 (≥1%) and 13 (22.4%) tumors had a PD-L1 expression of ≥ 50%. All of the patients received crizotinib as first line ALK inhibitor. Of the 44 patients evaluable for treatment response there was no significant difference in PFS between PDL1 negative cohort (median PFS - 13.8 months, CI 6.2-21.3 months) and PDL1 positive cohort (median PFS 10.9 months, CI 6.5-15.2 months, P-0.81). No association was seen between PD-L1 expression and PFS when PD-L1 expression levels were stratified by median or quartiles. In the subgroup analysis, PFS was not significantly different between different patterns of PDL1 expression or intensity of staining. Conclusions: In contrast to previous studies, we found a higher incidence of PD-L1 expression in patients with ALK rearranged advanced NSCLC. PFS on ALK inhibitors did not differ based on PD-L1 expression. However, this was a retrospective study in a limited number of patients. More prospective studies are needed to confirm our findings. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.